The change in electronic structure of oriented multilayer carbon nanotubes under action of pulsed ion beam of nanosecond duration - P. M. Korusenko; S. N. Nesov; S. N. Povoroznyuk (Омский научный вестник)
Using the equipment of the Russian-German channel of the RGL station (BESSY II, Germany), the Kratos Axis Ultra DLD laboratory spectrometer and the transmission electron microscope, data are obtained on the chemical state of MWCNTs and their structure after irradiation with a pulsed ion beam of nanosecond duration. It is shown that pulsed ion irradiation leads to the formation of new structural formations: thin nanotubes with an outer diameter of ~5 nm, structures up to ~ 20 nm in size, consisting of encapsulated iron clusters in a graphite shell, and also of a onion-like carbon with a characteristic size of ~5 nm. The formation of new structures is one of the reasons for the increase in the fraction of carbon atoms in sp3-hybridized in the surface layer of MWCNTs.